Status and Distribution of Bentinckia condapanna Berry Ex Roxb (Arecaceae), An Endemic Endangered Palm Species of the Southern Western Ghats, Tamil Nadu - Gnanasekar, S.; Vidhya, C.; Sivarathinavel, R. A.; Banu, S. Sumiya (Indian Forester, 2022)
The genus Bentinckia Berry is an excellent example for disjunction geographical distribution on the evolution of plant taxa at generic level in phytogeography. Bentinckia condapanna Berry ex Roxb. is an endemic and highly threatened Hill Areca nut palm of Southern Western Ghats of Kerala and Tamil Nadu. It is locally known as Condapana, Kanakamuku, Kattukamuku, Vareikamuku, Kanthakamuku, Parapakku. The taxon is a narrow endemic with limited natural distribution in the evergreen forests at an altitude around 1100 to 1900 m along the hills of Southern Travancore and Tirunelveli Hills of Southern Western Ghats. The critical habitat of the species is in slopes of inaccessible steep rocky cliffs. The species population is threatened by deforestation for agricultural expansion and competition with quick-growing exotic species, cattle grazing which impairs regeneration, forest fire damages mature individuals and fed by wild elephants. Owing to its highly restricted distribution and vulnerable status of this species, a forest exploration was piloted at Kalakadu Mundanthurai Tiger Reserve, Kanyakumari Wildlife Sanctuary and Kodaikanal Wildlife Sanctuary on this hitherto unknown population. Also a nursery experiment conducted to record the germination status which makes it more significant way for species recovery.